A novel route to the coupling of molecular dynamics and phase-field simulations of crystal growth. (May 2019) - Bollada, P C; Men, H; Fang, C; Jimack, P K; Fan, Z; Mullis, A M
Abstract: Molecular dynamic simulations, ab initio (DFT) calculations and experimental evidence suggests that there is a liquid-solid transition region which may be characterised by an order parameter. In this interface region the order parameter is not observed to be symmetrical, rather it tends to be steep on the solid side and exponentially decreasing on the liquid side. The order parameter in phase field computations is, to date, always assumed to give a symmetrical interface region. Hence, we ask how to extend the phase field model to give a profile that fits this data, and how such a model affects the simulation.